Comparison of congenital pulmonary airway malformation volume ratios calculated by ultrasound and magnetic resonance imaging. (1st October 2016) - Euser, Anna G.; Meyers, Mariana L.; Zaretsky, Michael V.; Crombleholme, Timothy M.
Abstract: Objective : To compare congenital pulmonary airway malformation (CPAM) volume to head circumference ratios (CVRs) determined by different imaging modalities and calculation techniques. Methods : Fetal thoracic lesion images by ultrasound (US) and magnetic resonance imaging (MRI) were retrospectively reviewed and the CVRs were calculated. The CVR US was determined by the standard method. The CVR MRI was calculated from T2-weighted sequences (HASTE/SSH-TSE) in two ways, dimensional measurements analogous to US technique (MRI-D) and by using a MRI-software calculated volume (MRI-V). CVR values between methods were compared using Wilcoxon matched-pairs signed-rank testing, Bland–Altman analyses, and Spearman correlations. Results : Appropriate images were available to compare CVR US to CVR MRI-D for 20 patients and CVR US to CVR MRI-V for 18 patients. There were no significant differences in CVR values between modalities. By Bland–Altman analyses, the CVR measurements were largely within the limits of agreement: 18 of 20 for CVR MRI-D and 17 of 18 for CVR MRI-V, with a slight bias towards larger measurements by MRI. Conclusions : Though values varied between modalities for individual patients, there was no systematic difference in CVRs determined by US or MRI. Fetal prognostic category for CPAMs did not change based on MRI in any patient in this series.